Caractérisation du parc agroforestier à Parkia biglobosa (Jacq.) R. Br. Ex G. Don en Basse Casamance (Sénégal) - Éric Arnaud Diatta; Bienvenu Sambou; Fatimata Niang-Diop; Malaïny Diatta (VertigO)
In Lower Casamance, Parkia biglobosa is one of the woody species integrated into the agricultural production system because of its socio-economic importance. Despite this importance, its population is experiencing serious threats from a combination of natural and anthropogenic factors. The purpose of this work is to characterize the woody flora and vegetation of P. biglobosa agroforestry parkland in Lower Casamance. To do this, a systematic inventory of crop fields was carried out in two villages using the Closest Individual (CI) method. This study identified 29 species from 27 genera in 13 botanical families in all two villages, 24 species in Kagnobon and 18 in Mangagoulack. The Shannon-Weaver Index shows low diversity across the two villages. The structural parameters are higher in Mangagoulack except regeneration and mortality of the species. The different structures show a young stand in Mangagoulack unlike in Kagnobon where the species faces a regeneration problem due to vegetation fires and the exploitation of seeds. Efforts could be made to preserve the regeneration of P. biglobosa and thus ensure its maintenance in the crop fields.